Molecular Detection of Anaplasma spp. and Ehrlichia spp. in Ruminants from Twelve Provinces of China - Haixiang Qiu; Patrick John Kelly; Jilei Zhang; Qinghua Luo; Yi Yang; Yongjiang Mao; Zhangping Yang; Jing Li; Hongzhuan Wu; Chengming Wang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Anaplasma spp. and Ehrlichia spp. are tick-transmitted bacteria that are of significant economic importance as they can infect large and small ruminants and also people. There is little information on anaplasmosis and ehrlichiosis in ruminants in China. 16S rRNA FRET-qPCRs were used to screen convenience whole blood samples from 2,240 domestic ruminants in 12 provinces of China for Anaplasma spp. and Ehrlichia spp. Positive samples were further analyzed with a standard PCR for the gltA. Anaplasma spp. DNA was detected in the sheep (11.7%; 13/111), goats (81.8%; 219/270), cattle (13.2%; 241/1,830), and water buffaloes (6.9%; 2/29). Ehrlichia spp. DNA was detected in sheep (1.8%; 2/111), goats (1.1%; 3/270), and cattle (3.6%; 65/1830) but not in water buffaloes (0/29). Sequencing of gltA PCR products showed that A. marginale, A. ovis, Ehrlichia canis, and Ehrlichia sp. (JX629807) were present in ruminants from China, while the 16S rRNA FRET-qPCR sequence data indicated that there might also be A. platys, A. phagocytophilum, Anaplasma sp. BL126-13 (KJ410243), and Anaplasma sp. JC3-6 (KM227012). Our study shows that domestic ruminants from China are not uncommonly infected with a variety of Anaplasma spp. and Ehrlichia spp.